EFFECTS OF SYNTHETIC ASTAXANTHIN, CHLORELLA, AND SPIRULINA SUPPLEMENTATION IN DIETS ON GROWTH AND PIGMENTATION OF KURUMOI RAINBOWFISH, Melanotaenia parva - Nina Meilisza; Muhammad Agus Suprayudi; Dedi Jusadi; Muhammad Zairin Jr.; I Made Artika (Indonesian Aquaculture Journal, 2020)
Several studies have recommended the supplementation of astaxanthin in the Kurumoi rainbowfish diet to enhance its color and growth. However, knowledge regarding the effects of naturally-sourced and synthetically-made carotenoids in fish diets is currently limited. This study’s objective was to compare the growth and color performances of Melanotaenia parva by supplementing fish feed with synthetic astaxanthin and natural carotenoids sourced from Chlorella and Spirulina. A total of 12 fish (weight of 1.27 ± 0.02 g and total length of 4.70 ± 0.07 cm) were stocked at a density of one fish per liter. Basal feed (B) was used as the control feed. The experimental feeds were: B added with different doses of synthetic astaxanthin (Carophyll® Pink 10% water-soluble) from low to higher doses as follows: 0.6 g kg-1 (AS-L), 2.6 g kg-1 (AS-O), and 5.1 g kg-1 (AS-H); and B added with natural carotenoids of Chlorella sp. (Ch) and Spirulina sp. (Sp) of 8.6 g kg-1 and 5.5 g kg-1, respectively. The experimental diets were given at satiation for 56 days at 8 am and 3 pm. The study results showed that the addition of synthetic astaxanthin at a dose of 2.6 g kg-1 could increase the fish growth up to 12% with carotenoid deposition in the fish fin of three times higher than that of the treatments without synthetic astaxanthin. This dose was considered the optimal dose to increase the fish’s growth performance and pigmentation compared with the high dose of 5.1 g kg-1. Despite having the same nutrient composition, natural carotenoids in Chlorella and Spirulina did not produce better results compared to the low dose of synthetic astaxanthin of 0.6 g kg-1.